EFFICIENCY OF PHYSICAL EDUCATION CURRICULA IN LIGHT OF ARTIFICIAL INTELLIGENCE REQUIREMENTS AMONG IRAQI UNIVERSITY STUDENTS - Finteel, Ali Kareem (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. This integration helps provide personalized learning experiences that take into account individual differences among students, through the analysis of educational data and the design of flexible learning pathways that support the development of digital skills and global digital literacy. Objectives. This study aims to examine the efficiency of physical education curricula in Iraqi universities in light of artificial intelligence (AI) requirements. Method. Using the descriptive method and a questionnaire as the main tool for data collection on an exploratory sample of (30) students and a main sample of (307) students. Results. The results indicated that the current curricula enhance students’ understanding of smart technologies in sports training and clarify the role of AI in performance analysis, while smart teaching and assessment support individual learning and data-driven decision-making. However, the application of AI faces challenges such as weak technological infrastructure, limited financial resources, and lack of technical awareness and training. Conclusion. Accordingly, it is recommended to develop curricula to meet AI requirements, improve teaching and assessment methods, and enhance infrastructure and resources to ensure effective implementation of modern technologies.